KINERJA BIROKRASI DALAM PENYALURAN PUPUK BERSUBSIDI DI KECAMATAN JOMBANG - Vivi Vidyanita (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Abstract: This research was conducted on the basis of situation developed in the community as well as the results of studies showing that the performance of public bureaucracy in Indonesia is still bad. Public bureaucracy must constantly improve professionalism in carrying out what the main tasks, functions, powers and responsibilities , particularly in providing public services. The purposes of this study are to describe and analyze the performance of the bureaucracy, support and barrier factors in public services at the Department of Agriculture Jombang in the implementation subsidized distribution of fertilizer in District of Jombang. The results showed that the bureaucracy in Department of Agriculture in the implementation distribution of subsidized fertilizer in District of Jombang is still not optimal. Not all problems can be solved with a good and satisfying service. Some of the problems that can be improved by the Department of Agriculture such as the price in the market is not in accordance with the price set by the government caused by the weak oversight, stalls that sell to farmers in outside the area coverage, the mindset of farmers who still use fertilizer overdose and bigotry against one particular type of fertilizer, the presence of officials who conduct illegal charges against official stalls, the bureaucracy is too long in the distribution of subsidized fertilizer. Keywords : Performance, service, subsidized fertilizer. Abstrak: Penelitian ini dilakukan atas situasi yang berkembang di masyarakat serta hasil penelitian yang menunjukkan bahwa kinerja birokrasi publik di Indonesia masih buruk. Birokrasi publik harus senantiasa meningkatkan profesionalisme dalam melaksanakan apa yang menjadi tugas pokok, fungsi, kewenangan dan tanggung jawabnya, utamanya dalam memberikan layanan masyarakat. Tujuan dari penelitian ini adalah untuk mendeskripsikan dan menganalisis kinerja birokrasi, faktor pendukung dan penghambat pelayanan publik di Departemen Pertanian Jombang dalam pelaksanaan distribusi pupuk bersubsidi di Kabupaten Jombang. Hasil penelitian menunjukkan bahwa kinerja birokrasi Departemen Pertanian Jombang dalam pelaksanaan distribusi pupuk bersubsidi di Kabupaten Jombang masih belum optimal. Tidak semua masalah bisa diselesaikan dengan pelayanan yang baik dan memuaskan. Beberapa masalah yang masih dapat ditingkatkan penanganannya oleh Departemen Pertanian Jombang antara lain harga di pasar yang tidak sesuai dengan harga yang ditetapkan oleh pemerintah yang diakibatkan oleh lemahnya pengawasan, kios yang menjual kepada petani di luar cakupan wilayahnya, pola pikir petani yang masih menggunakan pupuk secara berlebihan dan kefanatikan terhadap satu jenis pupuk tertentu, adanya pejabat yang melakukan pungutan liar terhadap kios resmi, birokrasi yang terlalu panjang dalam pendistribusian pupuk. Kata Kunci : Kinerja, pelayanan, pupuk bersubsidi.